USE OF CASE TECHNOLOGIES IN SOLVING PROBLEMS OF ECONOMIC CONTENT IN SECONDARY SCHOOL - Akymenko, Natalia; Papach, Olha; Yakovlieva, Olga (Physical and Mathematical Education, 2024)
Formulation of the problem. The tasks of economic content contribute to the development of mathematical subjects and key competencies of entrepreneurship and financial literacy for general secondary education students. Using modern educational technologies allows them to gain practical experience in applying mathematical knowledge and skills to perform economic and financial calculations. Materials and Methods. The article provides a brief analysis of foreign and domestic scientific and methodological sources on various aspects of the application of economic content tasks, compares model curricula in Algebra for grades 7-9 for the presence of economic content tasks in teaching specific topics, summarizes own pedagogical experience in teaching mathematics and the use of case technology. Results. The peculiarities of teaching "Numerical sequences" in grade 9 concerning implementing the NUS concept are determined. In the model curricula, economic content tasks are defined as a tool for the formation of subject mathematical competence; they are recommended to be used in the educational process as one of the types of academic activities, and the ability to solve them is one of the expected learning outcomes of students. The article describes case technology for students to gain practical experience in applying mathematical knowledge and skills to perform financial calculations. A case study on "Mortgage Lending" is presented to familiarize 9th-grade students with the basics of banking and the use of mathematical knowledge to make mortgage calculations using examples as close as possible to real-life situations. The type of case study created is a case situation that requires the student to analyze a problem and apply a specific mathematical apparatus (work with arithmetic and geometric progressions). Conclusions. The case study on "Mortgage Lending" diversifies didactic materials for the topic "Numerical Sequences." Using economic tasks in studying "Numerical sequences" contributes to a deeper and more conscious understanding of the need to master the mathematical apparatus. The introduction of case technology ensures the practical orientation of the educational process, has a positive effect on increasing students’ cognitive interest in learning mathematics, and forms students’ ability to navigate the realities of the surrounding reality and apply the acquired knowledge in practical activities.